DETERMINATION OF THE CONTENT OF PHENOLIC COMPOUNDS IN RUBUS L. EXTRACT USING THE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD (International journal of artificial intelligence, 2025)
In this study, the quantitative composition of phenolic compounds in the extract of Rubus L. was determined using the High-Performance Liquid Chromatography (HPLC) method. The Rubus L. plant is highly valued in traditional medicine as a medicinal raw material with immunostimulatory, antipyretic, and anti-inflammatory properties. The primary objective of this research was to determine the concentration of biologically active substances (phenols, flavonoids, and antioxidants) in the plant and to evaluate their pharmacognostic significance.An extract was prepared from Rubus L. leaves using 96% ethanol and the ultrasonic extraction method. The analysis was conducted using a “Shimadzu LC-40 Nexera Lite” high-precision chromatograph. Standard solutions of gallic acid, salicylic acid, rutin, quercetin, apigenin, and kaempferol were employed for calibration. The results showed that the extract contained the highest concentrations of quercetin (1.235 mg/100 g) and rutin (0.785 mg/100 g). These phenolic compounds possess strong antioxidant and anti-inflammatory properties, thereby enhancing the plant’s medicinal value.The findings indicate that Rubus L. represents a significant natural source of bioactive compounds with potential applications in the pharmaceutical and food industries. Furthermore, the study demonstrates the practical effectiveness of using the HPLC method for determining the chemical composition of medicinal plants.